The life history of Hayesiana triopus (Westwood, 1847), with taxonomic notes on both present and former species of the genus Hayesiana Fletcher, 1982 (Lepidoptera: Sphingidae) - Jiang, Zhuo-Heng; Xu, Zhen-Bang; Cheng, Wen-Da; Li, Yu-Fei; Hu, Shao-Ji (Zootaxa, 2023)
The two species previously included in the genus Hayesiana Fletcher, 1982 were studied. The life history of the sole currently included species, Hayesiana triopus (Westwood, 1847) is illustrated in colour for the first time. Field records of Hayesiana triopus and Dahira farintaenia (Zhu & Wang, 1997) (previously Hayesiana farintaenia) are given, with the first description of the female genitalia of the latter. The diagnostic features and DNA barcoding data of Hayesiana triopus and Dahira farintaenia are also discussed.